Description of Mother's Knowledge and Attitudes About Dental and Oral Health in Pre-School Children 3-4 Years Old at Bertha Inpatient Primary Clinic in 2023 - Krisdayanti Zalukhu; Anita Veronika; Risda Mariana Manik; Bernadetta Ambarita (Jurnal EduHealth, 2023)
Dental and oral health is an integral part of overall health that affects a person's quality of life. This study aims to describe the knowledge and attitudes of mothers who have preschool children aged 3-4 years at the Bertha Inpatient Primary Clinic in 2023. This research is a descriptive study using a survey method by distributing questionnaires. The sample of this study was 30 respondents from the mother at Bertha Primary Clinic who had preschool children aged 3-4 years, with the sampling technique that was using accidental sampling. Based on the research, it was found that the knowledge of respondents (mothers) regarding children's dental and oral health was in the good category, 14 respondents (46.7%), enough for 13 respondents (43.3.7%), and lacking for 3 respondents (10.0). %). And mother's attitude regarding children's dental and oral health with a positive category of 27 respondents (90.0%) and a negative category of 3 respondents (10.0%). Researchers suggest that mothers who have children increase their sources of information about dental and oral health by building partnerships with health workers or viewing social media. As well as implementing dental and oral hygiene since early childhood.